Association of vitamin D and its metabolites in patients with and without type 2 diabetes and their relationship to diabetes complications - Alexandra E. Butler; Soha R. Dargham; Aishah Latif; Haira R. Mokhtar; Amal Robay; Omar M. Chidiac; Amin Jayyousi; Jassim Al Suwaidi; Ronald G. Crystal; Charbel Abi Khalil; Stephen L. Atkin (SAGE Publishing, 2020)
Background: Epidemiological studies have suggested that vitamin D deficiency is associated with the development of type 2 diabetes (T2DM) and is related to diabetes complications. This study was undertaken to determine the relationship between diabetes complications and cardiovascular risk factors with vitamin D 3 and its metabolites: 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ), 25-hydroxyvitamin D 3 (25(OH)D 3 ), 24,25-dihydroxyvitamin D 3 (24,25(OH) 2 D 3 ); and 25-hydroxy-3epi-vitamin D 3 (3epi25(OH)D 3 ). Methods: 750 Qatari subjects, 460 (61.3%) with and 290 (38.7%) without T2DM, who were not taking vitamin D 3 supplements, participated in this cross-sectional, observational study. Plasma concentrations of vitamin D 3 and its metabolites were measured by liquid chromatography tandem mass spectrometry analysis. Results: T2DM subjects had lower concentrations of all vitamin D 3 metabolites ( p  < 0.001) except 3epi25(OH)D 3 ( p  < 0.071). Males had higher concentrations of all vitamin D 3 metabolites ( p  < 0.001). In the T2DM subjects, lower 25(OH)D 3 was associated with retinopathy ( p  < 0.03) and dyslipidemia ( p  < 0.04), but not neuropathy or vascular complications; lower 1,25(OH) 2 D 3 was associated with hypertension ( p  < 0.009), dyslipidemia ( p  < 0.003) and retinopathy ( p  < 0.006), and coronary artery disease ( p  < 0.012), but not neuropathy; lower 24,25(OH) 2 D 3 concentrations were associated with dyslipidemia alone ( p  < 0.019); 3epi25(OH)D 3 associated with diabetic neuropathy alone ( p  < 0.029). In nondiabetics, 25(OH)D 3 , 1,25(OH) 2 D 3 and 24,25(OH) 2 D 3 were associated with dyslipidemia ( p  < 0.001, p  < 0.001, p  < 0.015, respectively) and lower 1,25(OH) 2 D 3 was associated with hypertension ( p  < 0.001). Spearman's correlation showed 1,25(OH) 2 D 3 to be negatively correlated to age and diabetes duration. Conclusions: Different diabetes complications were associated with differing vitamin D parameters, with diabetic retinopathy related to lower 25(OH)D 3 and 1,25(OH) 2 D 3 levels, hypertension significantly associated with lower 1,25(OH) 2 D 3 , while dyslipidemia was associated with lower 25(OH)D 3 , 1,25(OH) 2 D 3 and 24,25(OH) 2 D 3. While 25(OH)D metabolites were lower in females, there was not an exaggeration in complications.